Spirit Komuniter-Ekaristis Sebagai Unsur Hakiki Cara Hidup Jemaat Perdana dan Relevansinya Bagi Gereja Masa Kini - Susang, Paulus; Daten, Marys; Kanaf, Gregorio; Benu, Gabriel; Senda, Siprianus Soleman (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The way of life of the early Church written in Acts 2:41-47 is a model of Christian life for the Church throughout the ages. The spirit that underlies this way of life is a communitarian-eucharistic spirit, namely a communion centered on Christ that is present in the eucharistic meal. The fundamental question regarding this is how this spirit was lived by the early congregation and inspired the Church today. To answer this question, this research was conducted using the literature study method. The research results are discussed using a descriptive analysis approach to provide an overview of the communitarian-eucharistic spirit lived by the early congregation and draw out its relevance for the Church today. In this way, this communitarian-eucharistic spirit can animate the life of the Church today in its liturgical duties, preaching, communion, service and witness of faith in contextual society.